Tobacco, corn and wheat for phytoremediation of cadmium polluted soil - Vijayaragavan3*, K. Chitra1, S. Sharavanan2 and M. (Recent Research in Science and Technology, 2011)
Tobacco (Nicotiana tabacum L.) corn (Zea mays L.) and wheat (Triticum aestivum L.) seedlings were grown in three cadmium (Cd) concentration levels (10, 30 and 50 mg kg-1) in a soil pot culture to analyze cadmium concentration, proline contents (leaves) and growth responses in the shoots and roots of corn, wheat and tobacco plants.The experiment was conducted at Botanical Garden, Department of Botany, Annamalai University, Tamil Nadu, during the period of January to March 2011. In the pot culture experiment. These plants were analysed on 15th sampling days, in soil amended with various levels of cadmium (viz, 10, 30 and 50 mg kg-1). The inner surfaces of pots were lined with a polythene sheet. Each pot containing 3kg of air dried soil. Six seeds were sown in each pot. All pots were watered to field capacity daily. Plants were thinned to a maximum of three per pots, after a week of germination. Root and shoot cadmium concentrations of corn, wheat and tobacco increased with their exposure to the cadmium levels and the highest cadmium concentration occurred in roots (except tobacco), followed by the shoot. The highest cadmium concentration was regarded in shoot then root of tobacco plants. An increase in proline in the leaves of corn, wheat and tobacco seedlings exposed to cadmium occurred as well as a decreased shoots and roots biomass. Thus, cadmium levels negatively affected the corn, wheat and tobacco seedlings growth. When compared to corn and wheat, tobacco plants are identified hyperaccumulators of cadmium in polluted soil.